Hubungan Pola Asuh Makan dengan Status Gizi Anak Balita dari Ibu Pengrajin Bambu di Desa Kebonsari Kecamatan Borobudur Kabupaten Magelang - Lusiana Retno Anggono; Artika Nurrahima (Jurnal Keperawatan Komunitas, 2015)
Nutritional status of children underfive are describes the state of balanced health as a result of consuming food that can be seen from the child's weight. Dietary pattern can be influence to the nutritional status of children. This research aimed to understanding the description of dietary pattern from mother’s child, nutritional status of children underfive and relation of dietary pattern and nutritional status of children underfive by bamboo craftmen mother in Kebonsari Village Borobudur District Magelang Regency. This research design was description corelatif non-eksperimental with cross sectional to 40 respondents by total sampling. Questioner and antropometric used to obtain the data of dietary pattern and nutritional status of children underfive. The research analize using Chi Square with level of significance p=0,05. The result showed p value=0,123, it means that dietary pattern applied by bamboo craftmen mother can’t give an effect to the nutritional status of children or in other words there is no significant relationship between dietary pattern with nutritional status of children underfive by bamboo craftmen mother in Kebonsari Village Borobudur District Magelang Regency. The result showed of 87,5 % respondent apply dietary pattern of autoritative, 10 % its authoritarian and 2,5 % its permissive. The result showed of 75 % nutritional status’s child is normal, 22,5 % it’s low and 2,5 % it’s obesity. Education and information about exactly dietary pattern and nutrition for children underfive must be upgrade by nurse of community. K